2020
DOI: 10.15850/amj.v7n3.1894
|View full text |Cite
|
Sign up to set email alerts
|

Response to Chemotherapy in Patients with Gestational Trophoblastic Neoplasia in A Tertiary Hospital in Indonesia

Abstract: Background: The incidence of gestational trophoblastic neoplasia (GTN) is high in Indonesia. Based on the FIGO prognostic score, GTN is classified into low-risk and high-risk categories. The high-risk group requires multidrug chemotherapy whereas the low-risk group requires single-drug chemotherapy. Response to chemotherapy would reflect the remission rate. The aim of this study was to describe the response to chemotherapy in GTN patients Methods: This was a cross-sectional descriptive retrospective study on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In a study in Bandung, Indonesia, 37 (58.7%) hydatidiform mole patients who had an interval of fewer than 4 months between the end of the last pregnancy and the first time they were diagnosed with GTN and received therapy had a greater risk of developing an invasive mole or GTN. 6 -hCG is the most used tumour marker for the diagnosis of GTN because it is more sensitive than other imaging techniques. The amount of beta-hCG produced by the chorionic tissue corresponds to the volume of this tumour.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in Bandung, Indonesia, 37 (58.7%) hydatidiform mole patients who had an interval of fewer than 4 months between the end of the last pregnancy and the first time they were diagnosed with GTN and received therapy had a greater risk of developing an invasive mole or GTN. 6 -hCG is the most used tumour marker for the diagnosis of GTN because it is more sensitive than other imaging techniques. The amount of beta-hCG produced by the chorionic tissue corresponds to the volume of this tumour.…”
Section: Resultsmentioning
confidence: 99%
“…18 One study grouped patients diagnosed with GTN according to FIGO prognostic factors and found that 63.6% were categorized as low-risk GTN and 36.4% as high-risk GTN. 6 The study by Sita-Lumsden et al 19 in London, based on the results of the FIGO prognostic assessment, 579 (94%) patients were in the low-risk category and only 39 (4%) patients were in the high-risk category. Likewise in this study, 49% of GTN had low risk, 39% had high risk, and the remaining 12% had no data.…”
Section: Resultsmentioning
confidence: 99%
“…4 Sementara itu, dilaporkan terdapat 730 kasus lama per tahun di RSUP Dr. Hasan Sadikin Bandung. 5 Berdasarkan panduan International Federation of Gynecology and Obstetrics (FIGO)/ World Health Organization Staging (WHO), TTG memiliki nilai skoring yang didapatkan melalui perhitungan skor dari faktor prognostik, yang dapat memengaruhi angka kejadian kasus TTG yaitu; usia pasien, riwayat kehamilan, interval waktu dengan kehamilan sebelumnya, peningkatan kadar β-hCG serum, memiliki ukuran tumor yang besar, tempat terjadinya metastasis, banyaknya jumlah tempat terjadinya metastasis, dan terdapat kemoterapi yang gagal sebelumnya. Dengan demikian, membagi TTG menjadi dua kelompok, TTG risiko rendah dan TTG risiko tinggi.…”
Section: Pendahuluanunclassified
“…Sedangkan, pada riwayat mola sendiri memiliki risiko yang tinggi dalam perkembangannya menjadi koriokarsinoma dan mola invasif. 5,8 Karena ketika seseorang memiliki riwayat mola hal ini akan memudahkan terjadinya disregulasi tumor suppressor genes. 9 Interval dengan kehamilan sebelumnya pada penelitian ini sering terjadi pada rentang 7 hingga 12 bulan.…”
Section: Pembahasanunclassified
“…Gestational trophoblastic neoplasia (GTN) is a type of gestational disease group of pregnancyrelated malignancies [1]. GTN incidence in developed countries is approximated to be one case per 40,000 pregnancies; meanwhile, in Indonesia, precisely in Hasan Sadikin General Hospital, as many as 730 cases are reported per year [2], [3]. GTN is generally highly sensitive to chemotherapy with a high cure rate of up to 90−100% [2], [4], [5].…”
Section: Introductionmentioning
confidence: 99%